Implementasi Sistem Keamanan Nirkabel Berbasis IoT Menggunakan Sensor Laser, ESP32, dan Platform ThingSpeak untuk Deteksi Intrusi Ruangan - Mohammad Roziqin; Sujono Sujono (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
Indoor security has become an increasingly important concern as digital technology continues to advance. Traditional alarm systems face two recurring limitations: the inability to support remote monitoring and the tendency of conventional motion sensors to produce false alarms under varying ambient temperatures. This study designs a room intrusion detection system using a laser beam as the trigger mechanism and an ESP32 microcontroller as the IoT-based control unit. The hardware implementation employs a Light Dependent Resistor (LDR) sensor with a 10-sample averaging technique to reduce signal noise, combined with hysteresis logic operating within a threshold range of 800 to 1100. The system is connected to the ThingSpeak cloud platform to enable real-time status updates. Testing across five lighting scenarios shows that the system reliably detects laser interruptions when LDR readings fall below 720 and returns to a safe state once readings exceed 1100. Security status updates were transmitted to the ThingSpeak dashboard with consistent HTTP responses (status code 200) for each condition change. These results indicate that ESP32 offers practical advantages in wireless connectivity and energy efficiency for a low-cost room security solution.